وحدة موضوع السورة وأهميتها في تدبر القرآن الكريم سورة تبارك نموذجا - Hameed, Afaf Abdul Ghafur (Maʿālim al-Qurʾān wa al-Sunnah, 2014)
This paper deals with the methodology of contemplating the Holy Quran. Among the numerous researchers who attempted to elucidate such methods is Sheik Abdul Rahman Habanaka Al Medani who presented 40 rules in his book entitled Kawad ALtadabur Alamthal Li Ketab Allah Azwajal (The Rules of Contemplating The Holy Quran). The second edition consists of 800 pages compared to the 200 pages of the original edition. Doubtless, continuous contemplation, observation, and research broadened the author's horizons thereby contributing to the differences between the two editions. The most significant rule highlighted in this paper is the unity of the surah's topic. Although Sheikh Abdul Rahman focuses on it as a second rule, it constantly emerges as an important consideration while discussing other rules. This is directly apparent in his discussion of partial changes' and their effect on the overall meaning, the coherence of the Quran's text. and the relation of verses to their ends. Indirectly, it can be noticed in the relation of a sentence to the topic of the chapter and the wisdom of having a Mekkan verse in a Madani chapter, among others. We discuss the issue of subject unity in two parts, namely theoretical and practical. The theoretical part discusses the rule subject unity, which emphasizes the coherence in a single theme permeating the surah, whilst the practical aspects focus on its implementation in Surat Tabarak. The aim of this research is to enhance contemplation of the Quran among the youths in order that it may be properly used to solve the many the many problems facing the Muslimah Ummah today, whilst also encouraging a better understand if the Quran.